Integrating HRM and Leadership: A Proposed Framework for Effective Leadership in Contemporary Organization - Muzammel Shah (Journal of Business & Tourism, 2021)
Despite the bulk of studies in the domain of leadership, there is still a dearth of agreement over what makes leaders effective. The objective of the present study is to address this gap by devising a model for leadership effectiveness in light of previous studies. The basic premise of the framework presented in this study is the same as Contingency leadership theory (Fiedler, 1964; 1967). To be successful, managers need to implement different leadership styles in different situations and that a particular leadership style would be most effective in specific circumstances. It is proposed that managers need to implement transactional or transformational leadership style and adopt associated HRM practices depending upon the level of LMX relationship which might lead to effective leadership in an organization. Effective people management requires that HR practices should be applied by a manager with a matching and consistent leadership style. Leadership effectiveness is enhanced if a manager uses a leadership style with supportive HR practices that best matches a particular group of subordinates. Moreover; uncovering the underlying relationship between HRM and leadership will help refine current methodological approaches in this area, guiding theoretical improvement and policy development related to HRM and leadership.